Cheeger inequalities for absorbing Markov chains. (September 2016) - Froyland, Gary; Stuart, Robyn M.
Abstract: We construct Cheeger-type bounds for the second eigenvalue of a substochastic transition probability matrix in terms of the Markov chain's conductance and metastability (and vice versa) with respect to its quasistationary distribution, extending classical results for stochastic transition matrices.